Vestibular Neurolabyrinthitis: A Follow-Up Study With Cervical and Ocular Vestibular Evoked Myogenic Potentials and the Video Head Impulse Test. (March 2014) - Magliulo, Giuseppe; Gagliardi, Silvia; Appiani, Mario Ciniglio; Iannella, Giannicola; Re, Massimo
Objectives: The aim of this study was to evaluate prospectively, in a group of patients affected by vestibular neurolabyrinthitis (VN), a diagnostic protocol including cervical vestibular evoked myogenic potentials (C-VEMPs), ocular vestibular evoked myogenic potentials (O-VEMPs), and the video head impulse test (vHIT). Methods: The diagnosis of VN was based on the patient's clinical history, an absence of associated auditory or neurologic symptoms, and a neuro-otological examination with an evaluation of lateral semicircular canal function by use of the Fitzgerald-Hallpike caloric vestibular test and the ice test. Results: In our series, 55% of the cases were superior and inferior VN, 40% were superior VN, and 5% were inferior VN. These cases, however, comprised different degrees of vestibular involvement, as the individual vestibular end organs have different prognoses. Four patients had only deficits of the horizontal and superior semicircular canals or their ampullary nerves. Conclusions: The implementation of C-VEMPs, O-VEMPs, and the vHIT in a vestibular diagnostic protocol has made it possible to observe patients with ampullary VN in a way that has not been feasible with other types of vestibular examinations. The age of the patient seems to have some impact on recovery from VN. When recovery occurs in the utricular and saccular nerves first and in the ampullary nerves subsequently, it may be reasonable to expect a more favorable outcome.